2019
DOI: 10.12991/jrp.2019.186
|View full text |Cite
|
Sign up to set email alerts
|

Screening of some Sumatran medicinal plants and selected secondary metabolites for their cytotoxic potential against MCF-7 and HSC-3 cell lines

Abstract: How to cite this article: Husnunnisa, Ismed F, Taher M, Ichwan SJA, Bakhtiar A, Arbain D. Screening of some Sumatran medicinal plants and selected secondary metabolites for their cytotoxic potential against MCF-7 and HSC-3 cell lines. J Res Pharm. 2019; 23(4): 770-776. ABSTRACT:In continuation of our study of Sumatran plants and bioactivities of their constituents particularly their cytotoxic activities, we re-extracted lichen Stereocaulon graminosum Schaer (Stereocaulaceae), and isolated atranorin (1) and sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
0
0
Order By: Relevance
“…Previously, studies related to pinostrobin showed that its cytotoxic activity against cancer cells was still low compared to anticancer drugs on the market. 2 , 8 , 9 Then supported by the research of Jones & Gehler (2020), pinostrobin selectively decreases the spread of but has less effect on cancer cell death. Although a lot of research has been conducted related to pinostrobin, research related to the modification of its structure is still very rare, especially in the compound pinostrobin propionate and pinostrobin butyrate (Figure 1B,C).…”
Section: Introductionmentioning
confidence: 87%
“…Previously, studies related to pinostrobin showed that its cytotoxic activity against cancer cells was still low compared to anticancer drugs on the market. 2 , 8 , 9 Then supported by the research of Jones & Gehler (2020), pinostrobin selectively decreases the spread of but has less effect on cancer cell death. Although a lot of research has been conducted related to pinostrobin, research related to the modification of its structure is still very rare, especially in the compound pinostrobin propionate and pinostrobin butyrate (Figure 1B,C).…”
Section: Introductionmentioning
confidence: 87%
“…In the exploration of sustainable Sumatran medicinal plants and the search for alternative medicines (6,7), mango leaves (Mangifera indica Linn.) have been reported…”
Section: Introductionmentioning
confidence: 99%